2022
DOI: 10.1177/23970022221083698
|View full text |Cite
|
Sign up to set email alerts
|

Forced to go virtual. Working-from-home arrangements and their effect on team communication during COVID-19 lockdown

Abstract: Working-from-home arrangements have become increasingly important for firms’ work organization. In this context, the COVID-19 pandemic has led to teams that previously did not work virtually being forced to interact and communicate virtually. In this study, we analyze changes in intra-team communication of four teams in a German medium-sized enterprise. Quantitative network analyses of email communication and qualitative analyses of interviews before and during the COVID-19 lockdown in spring 2020 show that fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Managers cannot change national cultures but can mitigate their effects, using a range of mechanisms for conforming team members' behaviours that are directly tied to organisational culture, such as organisational values, mission statements, ethical codes, rituals and ceremonies, business structures, strategy, leadership and technology. Organisational culture can be a factor in the integration of CCVTs since it can positively influence team identification, contributing to feelings of ownership and belonging and promoting social cohesion within the CCVT (Maurer et al, 2022). Team identification is a process by which an individual sees the team as part of itself and forms a psychological bond with the group (Connaughton and Daly, 2004).…”
Section: Organisational Culture For Developing a Sense Of Ownership A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Managers cannot change national cultures but can mitigate their effects, using a range of mechanisms for conforming team members' behaviours that are directly tied to organisational culture, such as organisational values, mission statements, ethical codes, rituals and ceremonies, business structures, strategy, leadership and technology. Organisational culture can be a factor in the integration of CCVTs since it can positively influence team identification, contributing to feelings of ownership and belonging and promoting social cohesion within the CCVT (Maurer et al, 2022). Team identification is a process by which an individual sees the team as part of itself and forms a psychological bond with the group (Connaughton and Daly, 2004).…”
Section: Organisational Culture For Developing a Sense Of Ownership A...mentioning
confidence: 99%
“…MNCs often recur to virtual teamwork to integrate the tasks developed by staff and supporting departments from headquarters, expatriates and local employees distributed in foreign subsidiaries (Henderson et al, 2018). The COVID-19 pandemic caused one of the fastest adaptations in the history of societies, moving many organisations and teams entirely to virtual work (Burkart, 2022;Maurer et al, 2022;Logemann et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For many organizations, face‐to‐face (FTF) interviews are no longer the only option. Alternative mediums such as using video‐conference software (e.g., Zoom, Teams, and Skype) and asynchronous video interview (AVI) platforms (e.g., HireVue, ModernHire, and Aon VidAssess) for interviewing job applicants are increasingly used in the selection process (Griswold et al, 2021; Maurer & Maurer, 2020). As an example, the two biggest AVI providers, Modern Hire and HireVue, claim to work with over half and a third of the Fortune 100 companies, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…First, it examines whether findings about how biased decisions based on country of origin or nationality using traditional selection methods (Derous et al, 2012; Petersen & Dietz, 2005; Veit & Thijsen, 2021) also take place in an AVI context. Such an investigation is particularly significant given that the COVID‐19 pandemic has forced many organizations to interview applicants primarily through online mediums (Maurer & Maurer, 2020). Second, extant research has generally compared interviewees from in‐group (e.g., local applicants) versus out‐group (e.g., one type of immigrant).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic fueled all these challenges, which caused turbulences in the market but also turned upside down the daily job and family routine for many employees (Kaushik and Guleria, 2020 ; Shirmohammadi et al, 2022 ; Chung et al, 2023 ; Leslie-Miller et al, 2023 ). First studies showed that self-managing processes and flat hierarchies helped handle the COVID-19 challenges, like the sudden remote work (Maurer et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%